1996
DOI: 10.1007/s002280050140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N -acetylcysteine(NAC) treatment on HIV-1 infection: a double-blind placebo-controlled trial

Abstract: Further controlled trials with NAC are needed to determine whether it has a beneficial effect in the treatment of asymptomatic HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 19 publications
2
42
1
1
Order By: Relevance
“…a P b.06 compared with HNE 5 AM. increase in the CD4/CD8 ratio [8] and a slower decline of the CD4 + T cell count [9]. In the present study, we demonstrated for the first time that PTCA protected against HNE-induced cytotoxicity, possibly mediated by GSH restoration, thereby confirming the important role of GSH in HNE-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…a P b.06 compared with HNE 5 AM. increase in the CD4/CD8 ratio [8] and a slower decline of the CD4 + T cell count [9]. In the present study, we demonstrated for the first time that PTCA protected against HNE-induced cytotoxicity, possibly mediated by GSH restoration, thereby confirming the important role of GSH in HNE-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 52%
“…In T lymphocytes, thiols play an important role in regulating cell proliferation and programmed cell death. The restoration of cellular glutathione (GSH) levels is known to modulate the effect of inflammatory cytokines and increase the CD4 + cell count of HIV-infected patients [8][9][10]. Several studies demonstrated an increase in human CD4 + T lymphocyte count after supplementation with antioxidants such as N-acetyl cysteine (NAC), oxothiazolidine carboxylic acid and vitamin E among patients with immune diseases, indicating that oxidative stress can affect human CD4 + T lymphocyte survival [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…To ameliorate these changes and their immunological consequences, we (Dröge, 1989;Dröge et al 1992) proposed treatment with a cysteine derivative such as N-acetyl-cysteine. Subsequently, the abnormal cysteine status of HIV-infected patients and simian immunodeficiency virus-infected macaques has been confirmed by other research groups (Eck et al 1991;Staal et al 1992;Hortin et al 1994;Akerlund et al 1996;Hack et al 1997;Walmsley et al 1997). Several groups also reported a significant decrease in the intracellular glutathione level of the peripheral-blood mononuclear cells from HIV-infected patients (Eck et al 1989; Roederer et al Herzenberg et al 1997;Jahoor et al 1999) and simian immunodeficiency virus-infected rhesus macaques (Eck et al 1991).…”
Section: Massive Loss Of Cysteine In Human Immunodeficiency Virus Infmentioning
confidence: 75%
“…Survival data for subjects who took NAC provide additional evidence supporting the finding that low GSB levels impair survival. Oral administration of NAC was recently shown to increase plasma cysteine levels in HIV-infected subjects with CD4 T cell counts above 200͞l blood (29). This 4-month study was too short to evaluate survival; however, NAC administration was shown to be associated with a significantly decreased rate of CD4 T cell loss during the trial period.…”
Section: Resultsmentioning
confidence: 98%